2011
DOI: 10.1371/journal.pone.0017665
|View full text |Cite
|
Sign up to set email alerts
|

Llama-Derived Single Domain Antibodies to Build Multivalent, Superpotent and Broadened Neutralizing Anti-Viral Molecules

Abstract: For efficient prevention of viral infections and cross protection, simultaneous targeting of multiple viral epitopes is a powerful strategy. Llama heavy chain antibody fragments (VHH) against the trimeric envelope proteins of Respiratory Syncytial Virus (Fusion protein), Rabies virus (Glycoprotein) and H5N1 Influenza (Hemagglutinin 5) were selected from llama derived immune libraries by phage display. Neutralizing VHH recognizing different epitopes in the receptor binding sites on the spikes with affinities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
164
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 34 publications
6
164
0
4
Order By: Relevance
“…Hultberg and collaborators have recently demonstrated the possibility of significantly increasing (up to 4,000-fold) the neutralization potency of sdAbs directed against the trimeric Env proteins of several viruses (H5N1 influenza virus, rabies virus, and Rous sarcoma virus) by designing bivalent and trivalent constructs of neutralizing sdAbs (22). This is probably explained by an avidity effect, multivalent sdAbs being able to bind several protomers of the single trimeric Env.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hultberg and collaborators have recently demonstrated the possibility of significantly increasing (up to 4,000-fold) the neutralization potency of sdAbs directed against the trimeric Env proteins of several viruses (H5N1 influenza virus, rabies virus, and Rous sarcoma virus) by designing bivalent and trivalent constructs of neutralizing sdAbs (22). This is probably explained by an avidity effect, multivalent sdAbs being able to bind several protomers of the single trimeric Env.…”
Section: Discussionmentioning
confidence: 99%
“…To create the remaining bivalent-protein genes (JM3x2, JM3x3, JM3x4, JM3x5, JM5x2, JM5x3, JM5x4, and JM5x5), PCR amplifications were performed using primers Trim1For (CTCGCGGCCCAGCCGGCC ATGGCCGAGGTGCAGCTG) and Trim1Rev (CCGCTGCCACCTCCC CCCAGGCCTGAGGAGACAGTGACCTG) to amplify the JM3 and JM5 genes, which were substituted for the first sdAb gene of previous constructs using the InFusion system (the cloning scheme is illustrated in Fig. S1 in the supplemental material) (22). All constructs were checked by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…By reconstituting the heavy-chain only J3 into an antibody format to produce J3-Fc, we demonstrated here that inhibition of cell-cell infection by J3 was not simply a product of its smaller size since J3-Fc is six times larger than J3 but was consistently better able to neutralise cell-associated and cell-free virus infection. Previous studies have shown bivalent VHH have increased affinity for antigen and potency of neutralisation [46,47]. This increase in potency is therefore likely due to avidity effects conferred by the bivalent nature of J3-Fc since the J3 HCAb was more potently neutralising of cell-free virus when compared to the VHH alone on a molar scale against eleven viruses from subtypes A, B, C and CRF AG and BC including transmitter/founder viruses.…”
Section: Discussionmentioning
confidence: 97%
“…Поливалентные наноантитела, состоящие из VHH-доменов, могут стать мощным инстру-ментом для терапии резистентных вирусных ин-фекций, обусловленных высокой вариабельно-стью вируса, в том числе ВИЧ, вирусов гриппа, гепатита В и некоторых других [12,67].…”
Section: наноантитела для терапии бактериаль-ных и вирусных инфекцийunclassified
“…Примером могут по-служить наноантитела лам, иммунизированных инактивированной антирабической вакциной Merieux HCDV (генотип 1). При этом мультиме-ризация этих моновалентных наноантител спо-собна многократно (на 3-4 порядка) увеличивать их нейтрализующие свойства [67].…”
Section: наноантитела для терапии бактериаль-ных и вирусных инфекцийunclassified